A logical model of HCP - Anatoly D. Plotnikov (International Journal of Mathematics and Mathematical Sciences)
For an arbitrary undirected graph G, we are designing a logical model for the Hamiltonian Cycle Problem (HCP), using tools of Boolean algebra only. The obtained model is a logic formulation of the conditions for the existence of the Hamiltonian cycle, and uses m Boolean variables, where m is the number of the edges of a graph. This Boolean expression is true if and only if an initial graph is Hamiltonian. In general, the obtained Boolean expression may have an exponential length (the number of Boolean literals) and may be used for construction of the solution algorithm.